Digital control strategy for SPWM MPPT of PV system with three-phase NPC three-level converter - Mahmoud Aref; Ismaiel Ahmed; Vladislav Oboskalov (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper is aimed at investigating MPPT of PV system controlled by SPWM which is generated by comparing sinusoidal wave with variable frequency sawtooth wave. Perturb and observe (P&O) method is used for MPPT control of PV system. NPC three-phase three-level converter with LCL filter is designed to produce output voltage with minimum total harmonic distortion (THD) and high efficiency. The simple and fast method to get MPP of PV system with variable irradiation is digital control where the maximum power point is obtained from look-up table for the values of optimum voltage that achieve the maximum power for each irradiance value is used for digital control signal in microcontroller. The output voltage harmonic of multi-level three-phase inverter is controlled using SPWM control. THD of output voltage of multi-level three-phase inverter is 22% of stand-alone and grid-connected PV system. Small rate LCL filter is used to limit voltage harmonics within medium and low voltage limits (5%). THD output voltage of LCL filter is 4.9% and 3.51% of stand-alone and grid-connected PV system respectively.